Analisis Cerpen “Jangan Salahkan Rahim Ibuku” Karya Fitryani Lail Menggunakan Pendekatan Objektif - Lismawati Lismawati (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the intrinsic elements in the short story Jangan Salahkan Rahim Ibuku by Fitryani Lail using an objective approach. The research method applied in this analysis is a descriptive qualitative method. The data source for this research is the short story Jangan Salahkan Rahim Ibuku by Fitryani Lail. The data collection techniques used in this research include reading and note-taking methods. The data analysis technique employed is the content analysis of the short story Jangan Salahkan Rahim Ibuku by Fitryani Lail. The results of the study reveal intrinsic elements such as the theme, characters and characterization, point of view, plot, setting, language style, and moral message.